The Arbuscular Mycorrhiza Rhizophagus intraradices Reduces the Negative Effects of Arsenic on Soybean Plants - Spagnoletti, Federico Nicolás (2015)
Arsenic (As) in soils causes several effects, including death. Arsenic toxicity in soybean plants (Glycine max) has been little studied. Arbuscular mycorrhizas (AM) increase the tolerance of host plants to abiotic stress, like As. We investigated the effects of AM fungi on soybean grown in As-contaminated soils. A pot experiment was carried out in a glasshouse, at random with five replications. We applied three levels of As (0, 25 and 50 mg As kg-1), inoculated and non-inoculated with the AM Rhizophagus intraradices). Plant parameters and mycorrhizal colonization were measured. Arsenic in the substrate, roots and leaves was quantified. Arsenic affected negatively the AM percentage of spore germination and hyphal length. Also As affected soybean plants negatively: in extreme treatment more than 77.47% reduction in aerial biomass, 68.19% in plant height, 78.35% in number of leaves 44.96% reduction in root length and delay the phenological evolution. Mycorrhizal inoculation improved all of these parameters, and decreased plant As accumulation (7.8 mgAs kg-1 to 6.0 mgAs kg-1. AM inoculation showed a potential to reduce As toxicity in contaminated areas. The AM fungi presents a dilution effect on plant As concentration and prevents As intake by roots, and improve soybean tolerance to As.